Study of association of CTLA4 gene variants to non‐anterior uveitis. Issue 5 (16th September 2015) - Leon Rodriguez, D. A.; Serrano Lopera, A.; Cordero‐Coma, M.; Márquez, A.; Fonollosa, A.; Ruiz‐Arruza, I.; Callejas, J. L.; García Serrano, J. L.; Díaz Valle, D.; Pato, E.; Cañal, J.; del Rio, M. J.; et al.
Abstract This study was undertaken to investigate the possible genetic association of functional CTLA4 polymorphisms with susceptibility to non‐anterior uveitis. Four hundred and seventeen patients with endogenous non‐anterior uveitis and 1517 healthy controls of Spanish Caucasian origin were genotyped for the CTLA4 polymorphisms rs733618, rs5742909 and rs231775, using predesigned TaqMan© allele discrimination assays. PLINK software was used for the statistical analyses. No significant associations between the CTLA4 polymorphisms and susceptibility to global non‐anterior uveitis were found. It was also the case when the potential association of these genetic variants with the anatomical localization of the disease, such as intermediate, posterior or panuveitis, was assessed. Our results do not support a relevant role of these CTLA4 polymorphisms in the non‐anterior uveitis genetic predisposition.